2021
DOI: 10.1093/advances/nmaa157
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Unsweetened Preloads and Preloads Sweetened with Caloric or Low-/No-Calorie Sweeteners on Subsequent Energy Intakes: A Systematic Review and Meta-Analysis of Controlled Human Intervention Studies

Abstract: Effects of isocaloric (sweetness differences but constant calories) preloads and isosweet (caloric differences but constant sweetness) preloads, as well as preloads that were neither isosweet nor isocaloric (sweetness and caloric differences) on subsequent ad libitum meal and total (preload + ad libitum) energy intakes were investigated. Thirty-five crossover studies were eligible for inclusion, representing 116 comparisons (41, isocaloric; 41, isosweet; and 34, neither isosweet nor isocaloric). References of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 83 publications
1
17
0
2
Order By: Relevance
“…Artificial LCS are frequently used in foods and beverages. In a recent meta-analysis, which included several human studies, Lee et al [ 33 ] analyzed the effects of unsweetened preloads and preloads sweetened with either LCS or caloric sugars on subsequent energy intake. The total energy intake after unsweetened preloads or after preloads sweetened with LCS followed by an ad libitum test meal was lower compared to preloads sweetened with caloric sugars.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Artificial LCS are frequently used in foods and beverages. In a recent meta-analysis, which included several human studies, Lee et al [ 33 ] analyzed the effects of unsweetened preloads and preloads sweetened with either LCS or caloric sugars on subsequent energy intake. The total energy intake after unsweetened preloads or after preloads sweetened with LCS followed by an ad libitum test meal was lower compared to preloads sweetened with caloric sugars.…”
Section: Discussionmentioning
confidence: 99%
“…The authors conclude that the caloric differences of the preloads rather than differences in sweetness account for the results. The preloads with caloric sugars possibly resulted in a satiation effect during the ad libitum test meal [ 33 , 34 ]. The meta-analysis included studies with different designs: (1) various LCS were included, including artificial and bulk LCS and caloric sugars, and (2) the test meal composition and the time between preload and test meal were variable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given this extensive literature on mechanisms, one might expect that there is an equally large and convincing body of evidence demonstrating the adverse effects of LES on humans, prompting the need for mechanistic understanding and explanations. Yet, every recent systematic review (SR) and meta-analysis of randomised controlled trials (RCTs) in humans—from acute studies of appetite and glycaemic responses through longer-term studies with anthropometric and glycaemic control endpoints—finds neutral or beneficial effects of LES, and almost no indications of adverse effects on these outcomes [ 2 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Thus, the stream of papers offering a multitude of mechanisms for the adverse effects of LES exists within the context of a wall of empirical evidence that fails to find any adverse effects to be explained.…”
Section: Perspectivementioning
confidence: 99%
“…These narratives can only be constructed on a foundation of a narrow selection of basic research and prior opinion, “confirmed” by uncritical reference to observational associations and mechanistic studies, further supplemented by speculation and assumptions. Meta-analyses using data from tens of human trials consistently show that exposure to LES reduces total energy intake vs. caloric sweeteners, and generally has neutral effects on total energy intakes relative to unsweetened (mainly water) controls [ 10 , 11 , 15 , 16 ]. Similarly, systematic reviews from a large body of human trials show that LES on their own or together with nutrient loads have no significant effect on subsequent glycaemic or insulinaemic responses [ 9 , 14 , 17 ].…”
Section: Perspectivementioning
confidence: 99%